IMMUNOMODULATORY ROLE OF LECTIN FROM PHASEOLUS VULGARIS (RAJMA BEANS/ RED KIDNEY BEANS) - DR SOMA CHAKI,; SAYANTANI BHATTACHARJEE, (International Journal of Pharma and Bio Sciences, 2016)
The seed of rajma beans (red kidney beans) were taken and extract was prepared. This extract was used and the amount of protein present in the sample was estimated by protein estimation by Bradford reagent. Hemagglutination test was performed on human blood [all four blood groups A, B, AB and O and blood group B showed highest agglutination. Hemagglutination inhibition was done using the extract and dextrose, maltose, arabinose and lactose was used as substrates. The physicochemical properties of the extract at different pH and temperature were evaluated. Human lymphocyte was isolated and cultured. The extract was added to the cell culture at different concentrations and incubated for 24 hours. Finally the extract showed immunosuppressive activity on the human lymphocyte. The extract was further added on cultured HEL 92.1.7 and observed for cytotoxicity. The extract showed greater cytotoxicity towards HEL 92.1.7 cell line compared to human lymphocyte cell culture.